HARMONISING HUMANITY WITH NATURE. - Trimarchi, Nat (Cosmos & History, 2025)
Mythology, as we know, is at the heart of everything. This paper advances an argument for creating harmony among humanity, and with nature, by changing how we 'world' reality in modern mythologising. The connection between metaphor, the person, and art is proposed as key, since artmaking and admiring presents our most powerful way of creating a mythology. Metaphor is the unique form of meaning productivity, originating in nature's 'semiotic freedom', which is fundamental to expressing human embodiment in a 'world'. Symbol merely represents; but metaphor places us in the realm of the part-whole relation simultaneously with the becoming-being polarity. These are processes inherent in all life and emerging consciousness, hence 'spiritual' phenomena (in the most scientific sense), producing what Peirce claimed as the evolution of thought toward Reason. And, equally, the key processes in artmaking. Though high mathematics is metaphoric, revealed religion is essentially symbolic; and arguably the highest 'spiritual' expression is made, not even in philosophical discourse, but through Art. Linking meaning with valuing, I show where neuroscience is helpful, but hamstrung, in accounting for the primacy of metaphor in art. Benefits of Paul Ricoeur's hermeneutic phenomenology and Max Scheler's philosophical anthropology over Lakoff & Johnson's more generalised 'experientialist' approach to metaphor are examined. Ricoeur's account of "symbolism's" confusion with metaphor here reveals that, to activate the 're-productive' imagination, art must present a 'proper' metaphoric utterance (as does Schelling's: T2024a & 2024b). This was distinguished from the 'productive' imagination's merely reflective engagement with symbol and concept; and later argued to move us 'beyond interpretation' as Bradley (2009) suggests necessary, via Peircian semiotics (T2024c). Further detailed exploration here of this key relation between metaphor, the person, and art, hence reveals how philosophical anthropology provides the basis for re-empowering art to transcend Danto's 'artworld'. Making it thus capable of producing a realistic collectivising Spirit able to inspire the essential longer term humanistic 'new deal' with Nature, that is much needed to avert our possible extinction or descent into 'posthuman' mechanism.